Confucianism and Firm Performance - Wang, Lisong; Zhang, Yongjie; Wang, LiNa; Fu, Jingkai (Frontiers in Physics, 2020)
This paper examines the impact of Confucian culture on the company’s operation performance, taking Chinese listed companies from 2000 to 2018 as the research object. The results show that: (1) Confucian culture provides legitimacy for the company's profit-seeking behavior and therefore helps to improve their operating performance; (2) Confucian culture can effectively improve the efficiency of supervision mechanism but weaken the marginal contribution of incentive mechanism to financial performance. This paper provides empirical evidence for the influence of Confucianism on company operation performance, broadening the understanding of the role of informal institutions in company finance and enriching the theory of “culture and finance”.